2020
DOI: 10.1111/famp.12614
|View full text |Cite
|
Sign up to set email alerts
|

The Black Lives Matter Movement: A Call to Action for Couple and Family Therapists

Abstract: The frequent police killings during the COVID-19 pandemic forced a reckoning among Americans from all backgrounds and propelled the Black Lives Matter movement into a global force. This manuscript addresses major issues to aid practitioners in the effective treatment of African Americans via the lens of Critical Race Theory and the Bioecological Model. We place the impacts of racism on Black families in historical context and outline the sources of Black family resilience. We critique structural racism embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 71 publications
0
65
0
1
Order By: Relevance
“…Many excellent ideas for anti-racist clinical practice have been proposed (see, e.g. Coard et al, 2004;Gaztambide, 2019Gaztambide, , 2021Kelly et al, 2020;Legha & Miranda, 2020;Maiter, 2009); further, a social justice framework is central to many models of counseling psychology (Hargons et al, 2017), social work (International Federation of Social Workers et al, 2012, and community psychology (Nelson & Prilleltensky, 2010). Here we highlight two themes of particular relevance to attachment-informed interventions.…”
Section: Imagining Anti-racist Clinical Practicementioning
confidence: 94%
“…Many excellent ideas for anti-racist clinical practice have been proposed (see, e.g. Coard et al, 2004;Gaztambide, 2019Gaztambide, , 2021Kelly et al, 2020;Legha & Miranda, 2020;Maiter, 2009); further, a social justice framework is central to many models of counseling psychology (Hargons et al, 2017), social work (International Federation of Social Workers et al, 2012, and community psychology (Nelson & Prilleltensky, 2010). Here we highlight two themes of particular relevance to attachment-informed interventions.…”
Section: Imagining Anti-racist Clinical Practicementioning
confidence: 94%
“…Additionally, culturally informed parenting instruction might incorporate strategies that acknowledge oppressive experiences of marginalized populations while also exploring assets and resilience. Within African American populations, research has shown the importance of validating racial trauma, while also educating families about Black cultural strengths and racial socialization practices as therapeutic resources and protective factors for children's adjustment (Anderson, McKenny, & Stevenson, 2018; Kelly, Jérémie‐Brink, Chambers, & Smith‐Bynum, 2020).…”
Section: Cultural Adaptations At the Intervention Levelmentioning
confidence: 99%
“…These assessments have typically focused on child abuse, interpersonal violence, major medical or stressful life events, and Adverse Childhood Experiences (ACEs) (Centers for Disease Control and Prevention, Kaiser Permanente, 2016). Similarly, practitioners are encouraged to inquire about the presence of cultural trauma and the relative impact on each family member and family processes (Evans‐Campbell, 2008; Kelly et al, 2020). Practitioners will want to know if there is an intergenerational transmission of values about interactions with court and legal systems that has resulted in heightened hypervigilance and reactivity.…”
Section: Cultural Adaptations At the Intervention Levelmentioning
confidence: 99%
“…The answers to such questions are not simple. Fortunately, we have recently seen a flourishing of work and writing in relation to larger system issues that includes many papers connected to the crises around COVID‐19 (Falicov et al, 2020; Fraenkel & Cho, 2020; Watson et al, 2020; Weingarten et al, 2020), as well as increased attention to racism (Anderson et al, 2019; Kelly et al, 2020) and immigration (López‐Zerón et al, 2020). Similarly, research seems to be beginning to extend further into attending to larger system issues and their impact (Bernal et al, 2019; Bornstein & Lansford, 2019; Chung et al, 2021; Ferguson & Evans, 2019; Hoang et al, 2020; López‐Zerón et al, 2020; Patterson et al, 2018; Zhang & Han, 2020).…”
mentioning
confidence: 99%